Drug-related problems and therapeutic adherence in patients with tuberculosis at the Rimac Maternal and Child Health Center - Ccencho, Carlos (2020)
The research aimed to determine the drug-related problems (PRM) caused by the negative results associated with the medication (NMR) and the level of treatment adherence to 12 outpatients (the age range was 3 to 64 years and whose male gender represented 58.33% and 41.67% female) with tuberculosis admitted to the tuberculosis strategy health service of the Rímac Maternal and Child Health Center, for a period of nine months, through the application of the Dader Method , PRMs were identified and the probability of adverse effects obtained the highest percentage (35.48%) among the PRMs detected, secondly, it occupied the dose, schedule and / or inappropriate duration (32.26%), thirdly it occupied the breach partial (22.58%) followed by others. 31 NMR were identified, that is, an average of 2.5 NMR per patient, 18 (58.1%) of effective NMR were detected, 12 (38.7%) of safety NMR and 1 (3.2%) of RNM of need. The RNM were associated in greater magnitude to the ineffectiveness of the treatment as first place and security was second. The pharmaceutical intervention was involved in the quantity of medications administered. The healthcare activity of the pharmacotherapeutic follow-up professional managed to identify and solve the problems related to the medications caused by the negative results associated with the medication, concretizing in the significant improvement of therapeutic adherence to the pharmacological treatment of patients with tuberculosis.